Optimus: A Dynamic Rewriting Framework for Data-Parallel Execution Plans - Ke, Qifa; Isard, Michael; Yu, Yuan (Eurosys 2013, 2013)
In distributed data-parallel computing, a user program is compiled into an execution plan graph (EPG), typically a directed acyclic graph. This EPG is the core data structure used by modern distributed execution engines for task distribution, job management, and fault tolerance. Once submitted for execution, the EPG remains largely unchanged at runtime except for some limited modifications. This makes it difficult to employ dynamic optimization techniques that could substantially improve the distributed execution based on runtime information. This paper presents Optimus, a framework for dynamically rewriting an EPG at runtime. Optimus extends dynamic rewrite mechanisms present in systems such as Dryad and CIEL by integrating rewrite policy with a high-level data-parallel language, in this case DryadLINQ. This integration enables optimizations that require knowledge of the semantics of the computation, such as language customizations for domain-specific computations including matrix algebra. We describe the design and implementation of Optimus, outline its interfaces, and detail a number of rewriting techniques that address problems arising in distributed execution including data skew, dynamic data re-partitioning, handling unbounded iterative computations, and protecting important intermediate data for fault tolerance. We evaluate Optimus with real applications and data and show significant performance gains compared to manual optimization or customized systems. We demonstrate the versatility of dynamic EPG rewriting for data-parallel computing, and argue that it is an essential feature of any general-purpose distributed dataflow execution engine.